ANALYSIS OF 6-MERCAPTOPURINE AND 6-METHYLMERCAPTOPURINE IN DRIED BLOOD SPOTS USING LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETRY AND ITS APPLICATION IN CHILDHOOD ACUTE LYMPHOBLASTIC LEUKEMIA PATIENTS - Supandi, Supandi; Harahap, Yahdiana; Harmita, Harmita; Andalusia, Rizka; Ika, Marlina (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: To analyze and validate 6-mercaptopurine (6-MP) and 6-methylmercaptopurine (6-MMP) in dried blood spots (DBS) using liquid chromatography-tandem mass spectrometry (LC/MS-MS). Methods: Bio-sampling dried blood spot with DBS-CAMAGÂ® paper diameter of 8 mm and extracted with acetonitrile-methanol (1:3) containing internal standard 5-fluorouracil (5-FU). Separation was performed with C18 column AcquityÂ® 1.7 Î¼m (2.1 mm Ã— 100 mm), with a mobile phase mixture of 0.1% formic acid in water 0.1% formic acid in acetonitrile with gradient elution and flow rate 0.2 ml/min. Mass detection was Waters Xevo TQD with positive electrospray ionization (ESI) for 6-MP, 6-MMP and negative ESI for 5-FU in multiple reaction monitoring modes. The ions of 6-MP was detected at m/z 153.09->119.09, 6-MMP at m/z 167.17->126.03, and 5-FU at m/z 129.15->42.05. Results: This method fulfill the requirements of selectivity, linearity, lower limit of quantification, accuracy, precision, carry-over, matrix effects, and stability which refers to the european medicines agency (EMEA) guidelines. The linearity of 0.99 was 26-1000 ng/mL for 6-MP and 6-MMP, respectively. The validated method was applied to two childhood ALL maintenance phase. Retrieved 6-MP levels of 10.37 pmol/8Ã—108 erythrocytes, respectively. The levels of 6-MMP gained 16.59 pmol/8Ã—108 erythrocytes, respectively. Conclusion: The developed LC/MS-MS method is valid to analysis 6-MP and 6-MMP in DBS simultaneous in vitro according to EMEA guidelines. The method was successfully applied to authentic capillary blood samples from two childhood patients with ALL in the maintenance phase.